2021
DOI: 10.1128/mbio.02980-21
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Color Haploid Genetic Screen Identifies Novel Host Factors Involved in HIV-1 Latency

Abstract: A reservoir of latently HIV-1-infected cells persists in the presence of combination antiretroviral therapy (cART), representing a major obstacle for viral eradication. Reactivation of the latent HIV-1 provirus is part of curative strategies which aim to promote clearance of the infected cells.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 104 publications
2
11
0
Order By: Relevance
“…In a different methodological approach, by using a prey-bait yeast system Pedro et al also identified novel HIV-1 LTR interactors. In other studies, such as CRISPR KO based screens ( 85 , 86 ), gene-trap mutagenesis ( 87 ) or (single cell)RNA-seq analysis on sorted latent vs active infected cells ( 88 , 89 ) the screen results identified putative targets that regulate HIV-1 latency and latency reactivation not only via direct binding to the LTR but also via putative indirect molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a different methodological approach, by using a prey-bait yeast system Pedro et al also identified novel HIV-1 LTR interactors. In other studies, such as CRISPR KO based screens ( 85 , 86 ), gene-trap mutagenesis ( 87 ) or (single cell)RNA-seq analysis on sorted latent vs active infected cells ( 88 , 89 ) the screen results identified putative targets that regulate HIV-1 latency and latency reactivation not only via direct binding to the LTR but also via putative indirect molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the differences in methodological approach and latency models, we found common hits identified by Catchet-MS and those in previously published studies. These include the helicase DDX5 ( 89 ), members of the TREX1 ( 90 ) and TREX2 complex ( 87 ), transcriptional regulators such as GON4L ( 86 ) and CBX3 ( 88 ), members of the proteasome complex ( 86 ), SP-related factors ( 91 ) and interferon related factors such as IRF2BP2 ( 87 , 91 ) and ISG15 ( 88 ). The identification of previously identified and characterized interactors serve as positive controls and justify the validity of our approach.…”
Section: Discussionmentioning
confidence: 99%
“…In our own work, we have recently shown in two independent unbiased omics studies that proteins involved in RNA metabolism are prominent regulators of HIV-1 latency ( Röling et al., 2021 ). Using a haploid genetic screen we identified close to 70 host genes that are putatively involved in promoting or maintaining HIV-1 latency.…”
Section: What’s Rna Got To Do With It? the Contribution Of Rna-bindin...mentioning
confidence: 99%
“…The discovery of chromatin modulators involved in HIV transcription has gained significant attention. Recently, the chromodomain helicase DNA-binding protein (CHD9) was shown to promote HIV-1 latency via direct association with the 5′-LTR [68 ▪▪ ]. Knock-down of CHD9 with shRNAs in J-Lat A2 and J-Lat 11.1 cells resulted in significant reversal from latency [68 ▪▪ ].…”
Section: Hiv-1 Transcription and Latency Regulationmentioning
confidence: 99%